IMMEDIATE RELEASE SOLID DISPERSION TABLET OF AZILSARTAN: FORMULATION STRATEGY TO ENHANCE ORAL BIOAVAILABILITY - TAMBOLI, JAMEER A.; MOHITE, SHRINIVAS K. (International Journal of Applied Pharmaceutics, 2020)
Objective: Objective of the present study was to develop an immediate release solid dispersion tablet to enhance oral bioavailability of Azilsartan. Methods: Solid dispersion of azilsartan was developed using Soluplus® as a novel solubility enhancer by the solvent evaporation technique. 32factorial design was used in a fully randomized order to study effect of amount of azilsartan and Soluplus on solubility (µg/ml) and % drug dissolved in 30 min. Prepared solid dispersion was evaluated for different micromeritic properties, saturation solubility, and wettability. Then solid dispersion of all the batches compressed into an immediate-release tablet using sodium starch glycolate as a super disintegrant. Developed tablet formulations were evaluated for various post-compression parameters and satisfactory formulation among these were further studied for Fourier-transform infrared spectroscopy (FTIR), Differential Scanning Colorimeter (DSC), X-Ray Diffraction (XRD), in vivo absorption and stability study. Results: Results of micromeritic properties of solid dispersion showed that good flowability, compressibility, wettability, and saturation solubility. Post compression parameters of immediate-release tablets were found to be in acceptable limits. Batch ASD2 containing 40 mg Diacerein and 80 mg of Soluplus showed maximum drug release i.e. 99.82 % within 30 min. Compatibility study using FTIR, DSC, and XRD showed that drug is compatible with Soluplus. In vivo absorption study showed that, 2.67 fold increase in Area Under Curve (AUC) as compared to plain Azilsartan. Relative bioavailability was found to be 267.11 %. Results of stability study indicate that developed formulations were stable at accelerated temperature and humidity conditions. Conclusion: Study concluded that solid dispersion using Soluplus as a solubility enhancer is a suitable formulation strategy to enhance solubility, dissolution, and bioavailability of poorly water-soluble drug-like Azilsartan.